Complete Genome Sequence of Pseudomonas chilensis Strain ABC1, Isolated from Soil - Valenzuela-Heredia, Daniel (Microbiol Resour Announc, 2020)
Here, we report the complete genome sequence of Pseudomonas chilensis strain ABC1, which was isolated from a soil interstitial water sample collected at the University Adolfo Ibañez, Valparaiso, Chile. We assembled PacBio reads into a single closed contig with 209× mean coverage, yielding a 4,035,896-bp sequence with 62% GC content and 3,555 predicted genes.